Atypical polypoid adenomyoma of the uterus. A report of eleven cases. - Kubelka-Sabit, Katerina; Prodanova, Irina; Zografski, George; Basheska, Neli (Springer, 2008)
Background: Atypical polypoid adenomyoma (APA) is a rare uterine polypoid tumor occurring in women in their reproductive age. Method: Eleven cases of atypical polypoid adenomyoma have been diagnosed at our department in the last five years (2003–2007). The mean age of the patients was 37 (range 26–46 years). The most common clinical diagnosis was abnormal uterine bleeding, leiomyoma or endometrial polyp. In one patient the clinical diagnosis was endometrial hyperplasia, while two were examined for primary sterility. In one case the diagnosis was established in a curettage material from a spontaneous abortion. Apart from the conventional hematoxylin and eosin, additional histochemical and immunohistochemical stainings were also performed. Results: Macroscopically, white-gray polypoid fragments measuring 0.5–2 cm were found in the curettage materials. Histologically, the APAs were composed of atypical endometrial glands surrounded by smooth muscle stroma. Squamous morules were a common finding. In three cases, the APA was accompanied by foci of invasive endometrial adenocarcinoma. The immunohistochemical stains confirmed the smooth muscle nature of the stroma (alpha-smooth muscle actin, desmin and caldesmon positive). The morules were positive for CD10 marker, whereas Ki-67 proliferative index was low (5–15%), except in the foci of invasive adenocarcinoma. All tumors were hormone responsive. One of the patients was surgically treated for advanced endometrial adenocarcinoma in FIGO IIIC stage. Complete regression of the disease after tumor extirpation and consecutive high-dosage progesterone therapy was achieved in four of the patients, in one the disease persisted after two years due to suboptimal therapy, whereas five were lost to follow up (four of which diagnosed in the last 10 months). Conclusion: APA is considered to be a benign form of mixed epithelial and mesenchymal uterine tumors. This tumor can be associated with sterility and rarely with endometrial carcinoma, therefore recognition and correct diagnosis of this entity is important.
Keywords: uterine corpus; atypical polypoid adenomyoma; histology; immunohistochemistry; prognosis; endometrial carcinoma